An Optimization Model of Banking Outlets Integration Based on the Network Comprehensive Analysis - Wang, Yong; Zhou, TA (Bulletin of Electrical Engineering and Informatics, 2015)
The distribution of real banking outlets is based on the establishment of branches according to administrative division, which is obviously not rational in distribution. Against this phenomenon, this paper first analyzes the major factors that affect the distribution of outlets. Then, based on complex network, it puts forward the distribution model of outlets. Finally, it analyzes the model. At the same time, the paper takes the banking outlets of China Construction Bank of Wuxi City, Jiangsu Province for example. It employs the model to distribute and integrate its banking outlets. As a result, the distribution after integrating is more rational than the previous distribution, which verifies the rationality of the model and the distribution method of banking outlets.